An evaluation on profitability performances of Islamic banking division / Mohd Afandi Abu Bakar - Abu Bakar, Mohd Afandi (Institute of Research, Development and Commercialization , Universiti Teknologi MARA, 2006)
In this paper an attempt is made to evaluate the profitability perfbrmance o1'lslamic barrking business from 1996 to 2005, with specific reference to Islamic Banking Division (lBD). In doing so. the financial ratio approach has been adopted to reflect the managerial efficiency of the Islamic banking firms. In this study eight financial ratios were computed to measure Islamic banking performance, namely the return on equity. return on asset, return on deposits, profit margin, asset utilization, net operating margin.operating expenses ratio and investment margin. This study shall consist of two parts.First, it looks at the profitability performance of IBD of selected financial institutions providing lslamic products in the conventional banks. Secondly, the study evaluates the impact of the interest rate movement on the Islamic banking performance, IBD in specific.